Regulation of the Cell Cycle, Apoptosis, and Proline Accumulation Plays an Important Role in the Stress Response of the Eastern Oyster Crassostrea Virginica - Li, Cui; Wang, Haiyan; Guo, Ximing (Frontiers in Marine Science, 2022)
Background Understanding how organisms respond and adapt to environmental changes is central to evolutionary biology. As a sessile organism that has adapted to life in estuaries and intertidal zones, the eastern oyster Crassostrea virginica can tolerate wide fluctuations in temperature and salinity and survive for weeks out of water. To understand the molecular mechanisms underlying the remarkable stress tolerance of the eastern oyster, we studied the transcriptomic changes induced by exposure to air and cold stress. Eastern oysters were maintained for 7 days under four conditions, namely, in seawater (normal) at 22°C, in air at 22°C, in seawater at 5°C and in air at 5°C, and then sampled for RNA sequencing. Results Transcriptomic analysis revealed that many genes involved in cell cycle progression and DNA replication were downregulated in oysters exposed to air and cold, which indicates that stress inhibits cell division. Exposure to air at 22°C induced a concerted inhibition of apoptosis through the upregulation of expanded inhibitors of apoptosis and the downregulation of caspases. Interactions between TNF and NF-κB signalling implied a reduction in the inflammatory response and immune functions. Key genes for proline production, fatty acid synthesis and chromosomal proteins were upregulated during exposure to low temperatures, which suggested that proline accumulation, energy conservation, and epigenetic modification of chromosomes are important for coping with cold stress. The upregulation of melatonin, FMRFamide, and neural acetylcholine receptors indicate the significance of the neurohormonal regulation of homeostasis. Conclusion These results show that air exposure and cold stress alter the expression of key genes for cell division, apoptosis, proline accumulation, fatty acid metabolism, neurohormonal signalling, and epigenetic modifications, suggesting regulation of these processes plays an important role in the stress response of the eastern oyster and possibly other marine molluscs. This study provides new insights into molecular mechanisms of stress response that are essential for understanding the adaptive potential of marine organisms under climate change.